LESLLA Learner Perspectives on their Emergent Writing Practices in English - Gonzalves, Lisa (LESLLA Symposium Proceedings, 2023)
There exists a wealth of skills LESLLA learners must acquire towards gaining the ability to write autonomously, yet we still know very little about the steps involved in their development. Some researchers have attempted to put themselves in the seat of the student, such as Jill Sinclair Bell’s notorious self-study as an English speaker learning Chinese print literacy; however as highly literate scholars it is likely impossible for us to truly understand the experience of developing first time print-literacy (in an L2!) in adulthood. While studies have been conducted which highlight LESLLA students’ own perspectives on their acquisition of L2 language and print literacy, there are a lack of studies which explore students’ thinking as they undergo this process. Addressing this gap, this study aimed to uncover LESLLA learners’ cognitive processes during emergent writing activities. Via individual interviews with four adult learners, the researcher elicited both retrospective and concurrent think-aloud protocols to gain deeper student perspective. Findings indicated that, while engaged in a copying activity, the students focused more aesthetics/visual value and quantity of the written words rather than spelling or meaning; while engaged in writing activities which required independent spelling, the students relied on a number of strategies, including recalling letter sequence or orthographic patterns, applying phonetic knowledge, as well as eliciting visual representations. Notably, the learners did not require a fully developed knowledge of grapheme-phoneme correlations to produce correctly spelled words. The results have implications for our understanding of the stages of emergent literacy acquisition in L2 adults.